2002
DOI: 10.1590/s0102-311x2002000300015
|View full text |Cite
|
Sign up to set email alerts
|

Estudo dos partos e nascidos vivos de mães adolescentes e adultas jovens no Município de Feira de Santana, Bahia, Brasil, 1998

Abstract: Data from the Brazilian Ministry of Health and the literature indicate that adolescents may be overrepresented in the prevalence of maternal morbidity and mortality and neonatal complications. This study focused on childbirth and live newborns among adolescent and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
27

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 8 publications
0
4
0
27
Order By: Relevance
“…Besides that, teenagers who did not attend school before becoming pregnant also presented low self-esteem and little expectation concerning their future, when compared to teenagers who left school during pregnancy. 18 Making inadequate use of prenatal care is also one of the characteristics of teenage pregnancy 1,5 that negatively infl uences the biological outcomes of the pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides that, teenagers who did not attend school before becoming pregnant also presented low self-esteem and little expectation concerning their future, when compared to teenagers who left school during pregnancy. 18 Making inadequate use of prenatal care is also one of the characteristics of teenage pregnancy 1,5 that negatively infl uences the biological outcomes of the pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Among the main already established factors, we can highlight variables related to demographics, education, sexual and contraceptive behavior, and psychosocial factors concerning the teenager and her family. The literature shows associated factors such as: adverse socioeconomic situation, 5,6 becoming sexually active early in life, 8,10,16 higher frequency of sexual intercourse, 11,20,21 lack of use or inconsistent use of contraceptive methods, 11,20 lower expectations on the part of the teenager concerning schooling and professional performance in the future, 9,10 among others. In regard to family functioning and structure, studies have shown significant associations between teenage pregnancy and low schooling of the father and/or mother, early pregnancy of the teenager's biological mother, dysfunctional family relationships, such as early death of the mother, and absence of a father fi gure.…”
Section: Introductionmentioning
confidence: 99%
“…Na Bahia, após analise de dados do sistema de informação de nascidos vivos referentes a 590 adolescentes de 10 a 16 anos, 1604 de 17 a 19 anos e 3.085 adultas jovens, verifi cou-se incidência de baixo peso ao nascimento nos grupos de 11,5; 10,5 e 8,9%, respectivamente 21 . O baixo peso ao nascimento foi mais freqüente entre as puérperas adolescentes, principalmente entre as precoces, quando comparadas às adultas jovens, com signifi cância estatística.…”
Section: Discussionunclassified
“…Apuramos menores taxas de recém-nascidos de baixo peso em relação aos achados de outros autores 23 . Ainda, no nosso estudo, encontramos maiores porcentagens de nascimento de baixo peso em relação aos estudos realizados por outros pesquisadores 18,21 .…”
Section: Discussionunclassified
See 1 more Smart Citation